Efficacy and Interindividual Variability in Motor-Cortex Plasticity following Anodal tDCS and Paired-Associative Stimulation - Strube, Wolfgang (Neural Plast, 2015)
Interindividual response variability to various motor-cortex stimulation protocols has been recently reported. Comparative data of stimulation protocols with different modes of action is lacking. We aimed to compare the efficacy and response variability of two LTP-inducing stimulation protocols in the human motor cortex: anodal transcranial direct current stimulation (a-tDCS) and paired-associative stimulation (PAS25). In two experiments 30 subjects received 1mA a-tDCS and PAS25. Data analysis focused on motor-cortex excitability change and response defined as increase in MEP applying different cut-offs. Furthermore, the predictive pattern of baseline characteristics was explored. Both protocols induced a significant increase in motor-cortical excitability. In the PAS25 experiments the likelihood to develop a MEP response was higher compared to a-tDCS, whereas for intracortical facilitation (ICF) the likelihood for a response was higher in the a-tDCS experiments. Baseline ICF (12 ms) correlated positively with an increase in MEPs only following a-tDCS and responders had significantly higher ICF baseline values. Contrary to recent studies, we showed significant group-level efficacy following both stimulation protocols confirming older studies. However, we also observed a remarkable amount of nonresponders. Our findings highlight the need to define sufficient physiological read-outs for a given plasticity protocol and to develop predictive markers for targeted stimulation.